Flexible Polycarbonate and Copoly(Imide-Carbonate)s-Based Frequency Selective Surface for Electromagnetic Shielding Application - A. Murugesan; S. Ramprabhu; P. Senthil Kumar (International Journal of Chemical Engineering)
Optically transparent polycarbonates (PCs) and Copoly(Imide-Carbonate)s (Co-PICs) were synthesized by the melt polycondenzation method. Rigid (imide) and flexible (-O- and –C(CH3)2−) moieties were incorporated in the structure of bisimide diol comonomer using 4-aminophenol and 4,4′-(4,4′-isopropylidenediphenoxy) bis(phthalic anhydride). The structural properties of synthesized comonomers and polymers were confirmed by 1H, 13C-NMR and FT-IR spectra. Thermal properties of polycarbonates and copolycarbonates were examined using DSC and TG analysis. Thermal properties (glass transition Tg and thermal decomposition (Td) temperature) of copolymers were enhanced without sacrificing properties of BPA-based PC (high transparency, ductility, and processability) by the incorporation of active functional bisimide diol comonomer (5–10 mole %) in the polycarbonate backbone. Different sets of PCs and Co-PICs thin film substrates were prepared by the solvent casting method and used to design frequency selective surface. The proposed flexible FSS offers shielding of 20 dB at 8.8 GHz. In addition, the FSS offers polarization independent operation with its symmetrical unit cell geometry.